2000
DOI: 10.1053/jhep.2000.19288
|View full text |Cite
|
Sign up to set email alerts
|

Virologic and Clinical Expressions of Reciprocal Inhibitory Effect of Hepatitis B, C, and Delta Viruses in Patients With Chronic Hepatitis

Abstract: Hepatitis B virus (HBV), hepatitis D virus (HDV), and hepatitis C virus (HCV) are responsible for the majority of chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma (HCC) cases worldwide. 1-4 Multiple HBV and HDV infection has been extensively investigated in past years and found to be associated with a fulminant course of acute hepatitis, with the more severe forms of chronic liver disease, and with a rapid progression to liver cirrhosis. 5-8 An inhibitory effect exerted by HDV on HBV replicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
164
5
5

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(198 citation statements)
references
References 45 publications
(57 reference statements)
24
164
5
5
Order By: Relevance
“…In our previous study, the more severe forms of chronic hepatitis were more frequently found in chronic HBV/HCV concurrent infection than in HBV infection alone or in HCV infection alone. 8 In compliance with this, Zarski 7 and Mohamed et al 29 report higher prevalences of cases with histologically proven liver cirrhosis among patients with chronic HBV/HCV concurrent infection than in those with HCV infection alone.…”
Section: Discussionmentioning
confidence: 86%
“…In our previous study, the more severe forms of chronic hepatitis were more frequently found in chronic HBV/HCV concurrent infection than in HBV infection alone or in HCV infection alone. 8 In compliance with this, Zarski 7 and Mohamed et al 29 report higher prevalences of cases with histologically proven liver cirrhosis among patients with chronic HBV/HCV concurrent infection than in those with HCV infection alone.…”
Section: Discussionmentioning
confidence: 86%
“…The explanation for this fi nding may be in the fact that patients with occult B infection would be infected with low levels of viral particles incapable of stimulating the immune system to form its antibodies (28) , or that, following acute infection patients present a progressive decline of these markers until their becoming undetectable in the serum (35) . Another hypothesis is the existence of mutating HBV strains which do not express neither antigens nor antibodies in the blood of this population of patients (18,32) .…”
Section: Discussionmentioning
confidence: 99%
“…Coinfection with HBV and HCV is associated with severe forms of liver disease including fulminant hepatitis [8]. Patients with concurrent HBV and HCV infection have a high propensity to progress toward liver cirrhosis and, compared with monoinfected patients, are at an increased risk of developing hepatocellular carcinoma (HCC) [4,[9][10][11][12]. Notably, viral interference is evident between HBV and HCV.…”
Section: Hbv and Hcvmentioning
confidence: 99%
“…Notably, viral interference is evident between HBV and HCV. Mostly, HCV exerts a suppressive effect on HBV and may enhance seroclearance of HBV antigens or even replace the preexisting virus as the agent for continuing hepatitis [4,10,12,13]. As the newcomer, HBV may also suppress the preexisting HCV [4,14].…”
Section: Hbv and Hcvmentioning
confidence: 99%